Implementasi Virtual Reality Berbasis Surround Screen Projection Pada Aplikasi Informasi Alat Pemantau Cuaca Bmkg - Irfan Noor Agdhian; Adam Hendra Brata; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Badan Meteorologi Klimatologi dan Geofisika (BMKG) in conducting weather forecast, climate and earth activities using weather monitoring equipments. Due to weather monitoring equipment limited access, means that not everyone can know the names, functions, and how the equipment works. Based on these problem, the development on the surround screen projection based virtual reality (VR) application, began. This application simulates the environment of monitoring equipment park which include the 3D objects of weather monitoring equipments. The data was collected by observing the weather monitoring equipments on BMKG station, to collect the photograph as reference for making 3D object and explanation of the equipments as reference for making narrative audio. 3D objects and narrative audio that has been created then gathered in a virtual reality (VR) environment and implemented into the form of Android applications. Usability testing from this application gets a range values from Good to Very Good and also the level of success in performing the task gets a range of 80-100%. Performance tests show frame rate values with range of 35-56 fps. Meanwhile, white box and black box testing prove this application has been in accordance with the design process. It can be concluded that VR BMKG application can add more insight and give a comfortable access to weather, climate and earth information especially on weather monitoring equipments owned by BMKG.